Internal control, risk and Sharīʿah non-compliant income in Islamic financial institutions - Mustafa Mohd Hanefah; Muhammad Iqmal Hisham Kamaruddin; Supiah Salleh; Zurina Shafii; Nurazalia Zakaria (Emerald Publishing Limited, 2024)
Indexed by Scopus